Annual U.S. healthcare expenditures attributable to cigar smoking between 2001 and 2018, overall and by payer - Xin Xu; Ghada Homsi; Sherry T. Liu; Jennifer M. Gaber; Naa A. Inyang; Brian L. Rostron; Caryn F. Nagler; James Nonnemaker (PLoS ONE, 2025)
Background In 2022, 3.7% of U.S. adults currently smoked cigars. This study assesses cigar-smoking-attributable fractions in U.S. healthcare expenditures and associated annual healthcare expenditures overall and by payer, including publicly funded healthcare programs. Methods Data were obtained from the 2000, 2005, 2010, and 2015–2017 National Health Interview Survey linked with corresponding panels from the Medical Expenditure Panel Survey data through 2018. The final sample (n = 53,733) was restricted to adults aged 25 + . Estimates from four-part models and data from the Personal Health Care component of the 2001–2018 National Health Expenditures Accounts were combined to estimate fractions of and annual healthcare expenditures attributable to cigar smoking. All models controlled for sociodemographic characteristics and health-related behaviors. Results During 2001–2018, an estimated 1.8% (95% CI = 0.9%–3.4%) or $29.7 billion annually of U.S. healthcare expenditures could be attributed to cigar smoking. Most of this was funded by other third-party health insurance programs, a mix of private and public payers (e.g., Department of Veterans Affairs). Conclusions Cigar smoking creates a preventable financial burden on the U.S. healthcare system. Health consequences associated with cigar smoking may remain after successful quitting. The findings underscore the importance of preventing initiation of cigar smoking and providing evidence-based cessation methods to reduce the health and economic burden of cigar smoking.